Right arch with prostaglandin-dependent coarctation and aberrant left carotid artery in a 22q11.2 deletion infant. (23rd August 2021) - Kobayashi, Kei; Harada, Gen; Shinkawa, Takeshi
Abstract: Right aortic arch in association with coarctation of the aorta and vascular ring is a rare anatomy. We present an infant with chromosome 22q11.2 deletion, who had the right aortic arch with retroesophageal aberrant left subclavian artery and left internal carotid artery. The left external carotid artery and right common carotid artery originated together from the ascending aorta as a bovine branch. The infant also had severe coarctation, which was prostaglandin dependent.